Ð¡Ð¾Ð²Ñ€ÐµÐ¼ÐµÐ½Ð½Ð¾Ðµ ÑÐ¾ÑÑ‚Ð¾ÑÐ½Ð¸Ðµ Ð¿Ñ€Ð¾Ð±Ð»ÐµÐ¼Ñ‹ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ñ Ð°ÑÐ¿Ð¾Ñ€Ð¾Ð³ÐµÐ½Ð½Ñ‹Ñ… Ð°Ð½Ð°ÑÑ€Ð¾Ð±Ð½Ñ‹Ñ… Ð±Ð°ÐºÑ‚ÐµÑ€Ð¸Ð¹ - Vysekantsev, I. P.; Gurina, T. M.; Kirilyuk, A. L.; Kudokotseva, E. V.; Biryukova, S. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
The cryopreservation conditions for asporogenic anaerobic bacteria of different genera have been experimentally established. The H3TA medium provides a high viability at experimental conditions with adding DMSO and thiourea. The storage of samples at temperature of liquid nitrogen during 5 years (observation term) had no effect on initial biological properties of bacteria.